Az állatok magánjogi státusza: Történeti és összehasonlító jogi vizsgálat - Lénárdné Maletics, Borbála (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2026)
The protection of animals and the development of the related legal environment is one of the most pressing issues of our time. The civil law status of animals is particularly important, alongside the more traditional public law and criminal law regulations governing the protection of animals. How animals are treated under civil law reflects the way we view them, and whether they are defined as objects or sentient beings can have an impact on animal protection legislation. In the context of the civil law status of animals, I analyze the Roman law roots of their legal assessment. I consider this particularly important given that Roman law had a decisive influence on the development of civil law in continental European legal systems, formed the basis of civil codes, and influenced legal practice even in countries that did not directly adopt it. The civil legal status of animals is currently a constantly changing area of jurisprudence that is the focus of research. In line with international trends, civil law regulations concerning animals are constantly evolving in Europe, emphasizing and recognizing the sentient nature of animals. In this paper, I examine the impact of the civil law status of animals on legal practice through a presentation of the case law of three countries: Austria, Switzerland, and Hungary. The differences between the civil law rules of these countries allow us to analyse the extent to how the legal status of animals as objects influences their treatment in civil law cases.